Estudo de interações proteína-ligante e do enovelamento de proteínas através de dinâmica molecular, modelos de estado de Markov, cálculos quânticos e descritores de reatividade - Santos, Acassio Rocha (2021)
In this thesis, we seek to evaluate aspects of the electronic structure of biological systems through thermochemical calculations and quantum reactivity descriptors (QCMDs). These studies were applied to two distinct biological problems: 1) protein-ligand interaction; 2) protein folding. Regarding the first work, we performed a study of candidates for ricin RTA subunit inhibitors, a cytotoxic protein produced in castor bean seeds Ricinus communis and belongs to the family of ribosome-inactivating proteins (type 2). It is one of the most potent biological toxins among those known, consisting of two subunits, RTA and RTB, joined by a disulfide bridge. We performed a study to assess the interactions between the ricin toxin A (RTA) subunit of ricin and some of its inhibitors using modern Semiempirical Quantum Chemistry and ONIOM Quantum Mechanics/Molecular Mechanics (QM/MM) methods. Two approaches were followed: (calculation of the binding enthalpies, DHbind, and reactivity quantum chemical descriptors, QCMDs). These approaches were compared with the respective half-maximal inhibitory concentration (IC50) experimental data, in order to gain insight into RTA inhibitors and verify which quantum chemical method would better describe RTA-ligand interactions. We found that single-point energy calculations of DHbind, with the PM6-DH+, PM6-D3H4, and PM7 semiempirical methods; as well as the DEbind, obtained via the ONIOM QM/MM method, presented a good correlation with the IC50 data. We observed, however, that the correlation decreased significantly when we calculated DHbind after optimizing the full atom geometry with all semi-empirical methods after full-atom geometry optimization with all semiempirical methods. Based on the results from reactivity descriptors calculations for the cases studied, we noted that both types of interactions, molecular overlap and electrostatic interactions, play significant roles in the overall affinity of these ligands for the RTA binding pocket. In the second study, we evaluated aspects of the electronic structure in the folding process of NTL9, BBA and a3D proteins. In this work we evaluated three fast folding proteins (NTL9, BBA and a3D) through DM, MSMs and global and local reactivity descriptors obtained through DFT-D3 calculations and PM7 semi-empirical method. The results showed that the MSMs were able to characterize in details several folding paths, providing information that made it possible to infer the type of mechanism of the studied systems. Data from quantum calculations indicated that the enthalpy of formation is a good reaction coordinate for the folding process. In addition, our results demonstrate that the integration of MD, DFT-D3, semiempirical method and quantum reactivity descriptors offers the potential to reveal key aspects in protein folding process that are not described by any other approach. It was observed that local hardness per residue is able to distinguish non-native from native-like structures, revealing that intrinsic aspects of electronic structure play a highly relevant role in protein folding process. This observation may be a signature on the electronic structure during protein folding.